Fluorescent anti-counterfeiting-encryption method for constructing perovskite quantum dot array based on in-situ synthesis of solid-phase photolithography

The in-situ synthesis of perovskite quantum dot arrays through solid phase photolithography addresses the limitations of traditional methods by achieving high-resolution, high-capacity encryption with flexible information management and enhanced security.

CN119144327APending Publication Date: 2024-12-17MINNAN NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311431319.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Current fluorescent anti-counterfeiting technologies based on static encryption have low encoding capacity and weak anti-cracking capabilities, and the preparation of perovskite quantum dot micro-patterns using traditional photolithography is hindered by incompatibility with polar solvents and complex processes.

Method used

A method involving in-situ synthesis of perovskite quantum dot arrays using solid phase photolithography, where a perovskite precursor mixed with polymethyl methacrylate is irradiated with a 254 nm ultraviolet light source to induce nanocrystal generation, eliminating the need for development and etching operations.

Benefits of technology

This method enables high-resolution, efficient production of perovskite quantum dot patterns with a display resolution of 1268 DPI and a theoretical information storage capacity of 10^7502051, allowing for flexible encryption and irreversible information erasure, enhancing anti-cracking and attack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144327A_ABST
    Figure CN119144327A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorescent anti-counterfeiting-encryption method for constructing a perovskite quantum dot array based on in-situ synthesis of a solid-phase photoetching method. The preparation method comprises the following steps: dissolving cesium perfluoroglutarate, lead oleate and hexabromocyclododecane in N, N-dimethylformamide, adding polymethyl methacrylate, heating and dissolving to obtain a mixed precursor solution, coating a glass substrate with the mixed precursor solution to obtain a precursor film, drying to remove N, N-dimethylformamide, and finally covering the precursor film with a pattern chromium mask plate to obtain the chromium-coated glass. And irradiating under a 254 nm ultraviolet lamp to obtain the CsPbBr3 fluorescent anti-counterfeiting array. According to the method, the perovskite nanocrystal fluorescent microarray is prepared in situ based on a photo-induced dehalogenation direct photoetching method, under the action of a mask plate, halogenated hydrocarbon is induced to dehalogenate through 254 nm ultraviolet light to generate halide ions and drive generation of perovskite nanocrystals, and perovskite nanocrystal fluorescent microarrays with different patterns can be obtained by adjusting the patterns of the mask plate. Developing, etching and other operations are not needed, and the method is very simple, convenient, efficient and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-counterfeiting, and specifically discloses a fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography. Background Art

[0002] Fluorescent anti-counterfeiting is one of the most popular anti-counterfeiting-encryption technologies. Currently, fluorescent anti-counterfeiting is mainly based on static encryption, and the encoding method is often relatively simple, with low encoding capacity, resulting in weak anti-cracking and anti-attack capabilities. Therefore, the development of dynamic anti-counterfeiting fluorescent anti-counterfeiting technology with diverse encoding forms and high encoding capacity will help improve anti-cracking and attack capabilities. With the development of micro-nano processing technology of fluorescent anti-counterfeiting materials, it is possible to integrate thousands of micron-level information units within the size of a chip to obtain fluorescent miniaturized anti-counterfeiting patterns, which makes the information capacity per unit area show an exponential growth, expanding the information capacity while also ensuring its security. Therefore, it is of great significance to prepare fluorescent anti-counterfeiting labels with miniaturized patterns and dynamic regulation capabilities.

[0003] Metal halide perovskite quantum dots have attracted much attention due to their excellent luminescence properties, such as high fluorescence quantum yield, narrow fluorescence emission peak, large molar absorption coefficient and good defect tolerance. They are considered to be a new generation of luminescent materials and are widely used in anti-counterfeiting-encryption, photoelectric detection, display and sensing. At present, there are many methods for preparing micro-patterned perovskite nanocrystals, such as inkjet printing, transfer method, laser direct writing, photolithography, etc. Among them, photolithography is an excellent patterning method that can achieve high resolution and large-area manufacturing at the same time. It can avoid the coffee ring problem in inkjet printing and particle contamination and sub-pixel problems in transfer method. In addition, compared with the complete set of laser equipment used in laser direct writing method, its ultraviolet light source cost is lower. Therefore, photolithography is considered to be the most suitable method for preparing micro-patterned (perovskite quantum dots) dot) PQD (one of the most promising technologies. This technology can be divided into two categories: traditional photoresist-assisted lithography and direct lithography. Traditional photoresist-assisted lithography first uses photoresist for patterning, and then deposits pre-synthesized quantum dots. However, due to the ionic salt characteristics of PQD, it is very easy to quench in polar solvents, and photoresists, developers, etchants or strippers contain a large amount of polar solvents, which makes them incompatible with traditional photolithography processes; direct lithography is to directly or indirectly synthesize perovskite quantum dots through light induction, while avoiding the damage of polar solvents to PQD. Haizheng Zhong et al. reported a direct in-situ photolithography strategy for PQDs based on photopolymerization catalyzed by lead bromide complexes. This method uses photolithography of perovskite precursors to perform patterning before PQD generation, avoiding the destruction of PQDs by polar solvents during the complex stripping process, and obtains high-quality micro-patterned PQDs, showing good application prospects. At present, the research on the preparation of PQD micro-array patterns based on photolithography is still in its early stages, and the development of simple, efficient, high-quality PQD micro-array patterns is still an important challenge in the field. Summary of the invention

[0004] The object of the present invention is to provide a fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography. A perovskite precursor containing a halogenated hydrocarbon is mixed with polymethyl methacrylate to prepare a photoresist, and a 254 nm ultraviolet light source is used as a light source. After irradiation exposure through a mask, the halogenated hydrocarbon undergoes photodehalogenation to produce halogen ions. Since the perovskite nanocrystal generation energy is low, the in-situ generation of perovskite nanocrystals can be induced, and different patterned perovskite nanocrystal fluorescent microarrays can be obtained without the need for development and etching operations, which has the characteristics of simple process and high efficiency.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography comprises the following steps: 1) Dissolve cesium perfluoroglutarate (Cs-HFG), lead oleate (Pb(OA)2) and hexabromocyclododecane (HBCDs) in N,N-dimethylformamide (DMF) to obtain a perovskite precursor solution; 2) Add polymethyl methacrylate (PMMA) to the perovskite precursor solution, heat and stir at 55-65°C until completely dissolved to obtain a mixed precursor solution, coat the mixed precursor solution on a glass substrate to obtain a perovskite polymer precursor film, and then transfer it to a vacuum oven to dry and remove N, N-dimethylformamide (DMF); 3) A patterned chromium mask was covered on the perovskite polymer precursor film and irradiated under 254 nm ultraviolet light to obtain a CsPbBr3 fluorescent anti-counterfeiting array.

[0006] Furthermore, the usage ratio of cesium perfluoroglutarate, lead oleate, hexabromocyclododecane, N, N-dimethylformamide, and polymethyl methacrylate is 0.06 mmol:0.06 mmol:0.1 mmol:2 mL:0.5 g.

[0007] Furthermore, the heating temperature in step 2) is 55-65°C.

[0008] Furthermore, in step 2), the coating method is spin coating with a rotation speed of 1000-1200 r / min.

[0009] Furthermore, in step 2), the temperature of the oven is 60-65° C., the pressure is 0.1 Mpa, and the drying time is 55-65 min.

[0010] Furthermore, in step 3), the irradiation time under the ultraviolet lamp is 30 to 35 minutes.

[0011] The present invention provides a method for synthesizing CsPbBr3 fluorescent array patterns in situ based on photoinduced dehalogenationbased direct photolithography (PDDP), wherein hexabromocyclododecane (HBCDs), lead oleate, and cesium perfluoroglutarate are used as precursors and mixed with polymer PMMA to prepare photoresist, and a 254 nm ultraviolet light source is used as a light source. After irradiation exposure through a mask, HBCDs undergo photodebromination to produce a bromine source. Since the generation energy of CsPbBr3 nanocrystals is low, CsPbBr3 nanocrystals can be induced to be generated in situ, so different miniaturized patterns can be obtained using different masks. The preparation process of the method is simple, and only ultraviolet light source irradiation is required, and other operations such as development and etching are not required, so that PQDs with micron-level patterning can be obtained, which greatly reduces the production cost and efficiency of micron-level patterned PQDs. Currently, based on this strategy, a patterned PQD consisting of a square pixel array with a diameter of 20 μm can be obtained, with a display resolution of up to 1268 DPI and a theoretical information storage capacity of 10 7502051 . In addition, the information encryption method is flexible. By using the anti-counterfeiting-encryption method combining micro information with macro information, the present invention can successfully construct a macro-micro fluorescent anti-counterfeiting pattern of micron-level information units, and the fluorescent anti-counterfeiting pattern can be dynamically read under two channels, 254nm and 365nm, that is, the information can be repeatedly read more than 200 times under a 365nm ultraviolet lamp without damaging its encrypted information; and when it is necessary to controllably eliminate its information, the microscopic encrypted information can be eliminated under the 254nm information reading channel to achieve an anti-counterfeiting effect of "burning after reading", thereby greatly improving its anti-cracking and attack capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Schematic diagram of the preparation process of CsPbBr3 fluorescent anti-counterfeiting array film based on PDDP strategy; (a) Schematic diagram of direct in situ photolithography for making patterned PQDs; (b) Fluorescence image of green CsPbBr3PQD pattern (20 μm square matrix) prepared by direct in situ photolithography; (c) Transmission electron microscope cross-sectional image of CsPbBr3PQD pattern prepared by direct in situ photolithography; (d) HRTEM image of a single CsPbBr3PQD prepared by direct in situ photolithography; (e) Fluorescence emission spectrum, UV absorption spectrum, fluorescence quantum yield of solid film and photos of the synthesized CsPbBr3PQD under fluorescent light and UV light; (f) TRPL decay curve obtained by exciting CsPbBr3PQD at 375 nm; (g) Stability of the synthesized CsPbBr3 patterned PQD in water.

[0013] Figure 2 , (a) is a photo of a patterned PQD composed of array pixels under ultraviolet light and its microscopic pixels; (b) is a circular array with a diameter of 20 μm under a 365nm ultraviolet light; (c) is a square array with a diameter of 20 μm under a 365nm ultraviolet light; (d) is a strip array under a 365nm ultraviolet light; (e) is a letter-shaped patterned PQD; (f) is a photo of the emblem of Minnan Normal University with a diameter of 1.5 mm under a fluorescence microscope; (g) is a photo of the emblem of the School of Chemistry and Chemical Engineering of Minnan Normal University with a diameter of 1.5 mm under a fluorescence microscope; (h) is a photo of the Suzaku pattern with a diameter of 1.5 mm under a fluorescence microscope.

[0014] Figure 3 , (a) is a photo of the encryption film encoded in ASCII under a fluorescent light (left) and an ultraviolet light (right); (b) is a photo of the encryption film encoded in ASCII under a fluorescent microscope; (c) is a photo after the microscopic digital information is erased by photolithography; (d) is a photo of the encryption film encoded in Morse code under a fluorescent light (left) and an ultraviolet light (right); (e) is a photo of the encryption film encoded in Morse code under a fluorescent microscope; (f) is a photo after the microscopic Morse code information is erased by photolithography. Implementation

[0015] Some of the experimental materials involved in the present invention are as follows: Cesium perfluoroglutarate (Cs-HFG, ≥97%), lead oleate (Pb(OA)2, 99%), N, N-dimethylformamide (DMF, 99.8%), hexabromocyclododecane (HBCDs, 95%), and polymethyl methacrylate (PMMA) were purchased from Macklin. Cesium hydroxide solution (CsOH, 50 wt. % in H2O) was purchased from Aladdin, and isopropanol and anhydrous ether were purchased from Shantou Xilong Technology Co., Ltd., China. All reagents were used as received without further purification.

[0016] The fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography comprises the following steps: 1) Dissolve cesium perfluoroglutarate (Cs-HFG), lead oleate (Pb(OA)2) and hexabromocyclododecane (HBCDs) in N,N-dimethylformamide (DMF) to obtain a perovskite precursor solution; 2) Add polymethyl methacrylate (PMMA) to the perovskite precursor solution, heat and stir at 55-65°C until completely dissolved to obtain a mixed precursor solution, spin-coat the mixed precursor solution on a glass substrate at 1000-1200 r / min to obtain a perovskite polymer precursor film, and then transfer it to a vacuum oven at a temperature of 60-65°C and a pressure of 0.1 Mpa, and dry it for 55-65 min to remove N, N-dimethylformamide (DMF); 3) Cover the perovskite polymer precursor film with a patterned chromium mask and irradiate it under a 254 nm ultraviolet lamp for 30-35 min to obtain a CsPbBr3 fluorescent anti-counterfeiting array.

[0017] Furthermore, the usage ratio of cesium perfluoroglutarate, lead oleate, hexabromocyclododecane, N, N-dimethylformamide, and polymethyl methacrylate is 0.06 mmol:0.06 mmol:0.1 mmol:2 mL:0.5 g. Example 1

[0018] Fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography 1) Cs-HFG (0.06 mmol), Pb(OA)2 (0.06 mmol) and HBCDs (0.1 mmol) were dissolved in DMF (2 mL) to obtain a perovskite precursor solution. 0.5 g of polymer (PMMA) was added to the precursor solution and heated and stirred at 60 °C until completely dissolved to obtain a mixed precursor solution. The mixed precursor solution was spin-coated on a glass substrate at a speed of 1000 r / min to obtain a perovskite polymer precursor film, which was then transferred to a vacuum oven and DMF was quickly removed at 60 °C and low pressure (0.1 MPa) (60 min).

[0019] 2) A patterned chromium mask was covered on the perovskite polymer precursor film and irradiated under 254 nm ultraviolet light for 30 min to obtain a CsPbBr3 fluorescent anti-counterfeiting array.

[0020] 3) Macroscopic fluorescence images were obtained by naked eye observation under 365nm ultraviolet light, and microscopic fluorescence images were obtained by observation under a microscope.

[0021] Figure 1 The preparation process of CsPbBr3 fluorescent anti-counterfeiting array film based on PDDP strategy is demonstrated. Figure 1As shown in a, the DMF solution containing Cs-HFG, Pb(OA)2 and HBCDs perovskite precursor is fully mixed with PMMA polymer, and then a uniform perovskite polymer precursor film is obtained by spin coating, and the polar organic solvent DMF in the film is removed by vacuum drying, and then the CsPbBr3 fluorescent anti-counterfeiting array is prepared in situ by 254 nm UVC irradiation under a mask. Since lead halide perovskite has a low formation energy, when UVC is irradiated, the C-Br bond in HBCDs breaks to generate Br - and rapidly generate CsPbBr3 perovskite nanocrystals with cesium perfluoroglutarate and lead oleate. Unlike the previously reported photolithography preparation, the synthesis method based on the PDDP strategy does not require the stripping and removal of excess photoresist, which greatly simplifies the preparation steps. Figure 1 As shown in Figure b, the obtained product shows an arrayed CsPbBr3PNCs green fluorescent film with 20 μm square pixels under a fluorescence microscope, and its display resolution DPI can reach 1268. Through transmission electron microscopy (TEM) characterization of the cross-section of the luminescent area, it can be seen that the generated CsPbBr3PNCs are relatively uniformly distributed in the polymer matrix, with an average particle size of about 6.34 nm, and obvious lattice fringes can be observed through high-resolution TEM (HRTEM) images, with a spacing of about 2.5 Å, indicating that the obtained CsPbBr3PNCs have good crystallinity. The optical properties of the CsPbBr3PNCs film were further characterized, showing an obvious exciton absorption peak at 515 nm, corresponding to a maximum fluorescence emission wavelength of 521 nm, and the half-peak width of its fluorescence emission peak was only 22 nm, and the fluorescence quantum yield of the film could reach 51.1%, indicating that the CsPbBr3 fluorescent anti-counterfeiting array film synthesized based on the PDDP strategy has good luminescence performance ( Figure 1 e). In addition, since the PDDP strategy does not require the removal of excess photoresist, the prepared film has good integrity and exhibits excellent stability. After the film is immersed in water for 60 days, its fluorescence peak intensity does not decay. Example 2

[0022] Based on the simplicity of preparing CsPbBr3 nanocrystal fluorescent arrays by PDDP strategy, the present invention further uses mask lithography to prepare other high-resolution, strong-luminescence CsPbBr3 nanocrystal fluorescent array films, in order to explore its application in high-capacity macro-micro fluorescent dynamic anti-counterfeiting. Due to the high C-Br bond energy in HBCDs, the bond is induced to break and release Br under 254 nm UVC irradiation. - Thus, the growth of CsPbBr3PNCs is induced, but the C-Br bond cannot be broken under 365 nm UVA irradiation, so the fluorescence information can be read at 365 nm. Figure 2As shown in a, a 3×3 cm array film can be prepared by the PDDP strategy, which can emit bright green fluorescence under 365 nm ultraviolet light. The microscopic pattern is observed using a fluorescence microscope, and circular pixels with an internal diameter of 20 μm can be seen. In addition, the pixels can be changed arbitrarily according to the array pattern in the mask. Figure 2 BD demonstrated circular arrays with a diameter of 20 μm, square columns, and 60×1200 μm strip array pixels. Each pixel emits light evenly and has clear and sharp edges, showing satisfactory results. This strategy can also be further applied to the production of periodic square arrays required for displays and sensors. In addition to matrix pixels, several exquisite patternings were also produced through the mask, such as Figure 2 As shown in eh, the "MNNU" with a height of 200 μm and the "LFM laboratory" with a height of 100 μm, and the emblem of the School of Chemistry of Minnan Normal University, the emblem of the School of Chemistry and Chemical Engineering of Minnan Normal University and the Suzaku pattern with a diameter of 1.5 mm, the minimum line width of several patterns is as low as 14 μm, and the overall luminescence is uniform and the edges are clear, and the specific details of the pattern are not lost, which fully verifies the feasibility of manufacturing macro-micro patterned CsPbBr3 nanocrystal fluorescent arrays under this strategy. In addition, in addition to the PMMA polymer matrix, the present invention also explores the feasibility of PVDF electrospinning flexible film. The results show that PVDF membrane can also obtain a good CsPbBr3 nanocrystal fluorescent array. The above results fully illustrate the strong degree of freedom and imaging ability of preparing CsPbBr3 nanocrystal fluorescent arrays based on the PDDP strategy, laying a good foundation for subsequent macro-micro dynamic anti-counterfeiting. Example 3

[0023] Based on the above research, the present invention designs two encryption-anti-counterfeiting methods that combine macro information with micro information. Under a specific mask, two encryption patterns are formed after 254 nm ultraviolet lithography is completed, such as Figure 3 As shown in a, under fluorescent light, it can be seen that it is a transparent film. Under 365 nm ultraviolet light, the macro information "0100" "0100" "0100" "0101" can be seen. When the green area is further observed using an optical microscope, it can be observed that the area is composed of thousands of groups of microscopic fluorescent sequences "1101111011100101" ( Figure 3 b) According to Carro-Temboury' theory, its theoretical capacity is as high as 10 7502051. When both the macroscopic and microscopic information are obtained, they can be decrypted. First, in the microscopic pattern, an overall sequence can be divided into four groups of numbers by taking every four numbers from left to right, which are 1101 / 1110 / 1110 / 0101. Then combine the first row of the macroscopic pattern with the corresponding first group of numbers of the microscopic pattern to form an eight-digit sequence, and you can get the four number series "01001101", "01001110", "01001110", and "01010101". Finally, by performing ASCII decoding on these four number series, you can get the correct information, which is the four letters "MNNU". After obtaining the information, through 254 nmUVC irradiation, the precursor in the original mask shielding area is driven by light, CsPbBr3PNCs begin to grow, the patterned array disappears permanently, and the information is irreversibly erased. Such as Figure 3 As shown in Figure c, the microscopic information is destroyed after only 5 minutes and cannot be read. However, 365nm UVA can read the information repeatedly. If the single reading time is 10 seconds, it can be read repeatedly for more than 200 times. This shows the flexibility of the anti-counterfeiting strategy and greatly increases the difficulty of being imitated. In addition to binary coding, macro-micro information can also be encrypted using Morse code, such as Figure 3 The macro pattern in d needs to be decoded using Morse code. The specific process is as follows: first, convert the two groups of letters "TTTE" and "TEIT" into two groups of Morse code "- - -·" and "-···-", then regroup every two characters of the first group to get "- -" and "-·", and then decode the two characters in Morse code twice to get the two letters "MN", and regroup the first two characters and the last three characters of the second group to get "-·" and "··-". Similarly, the two letters "NU" can be obtained through Morse code decoding. In addition, by observing the green area, a microscopic Morse code "·· - -·· -··· -" array can be obtained. The information can be divided into four groups through the spacing in the pattern, namely "··-", "-", "··-", and "···-". Decoding the symbols of each group with the digital short code in Morse code can get the four numbers "2023". Finally, the final password is "MNNU 2023". It can also be irreversibly erased, such as Figure 3 As shown in Figure e, after continuing the photolithography without adding a mask for 5 minutes, the microscopic information is basically unreadable.

[0024] The present invention has developed a new strategy for in-situ preparation of perovskite nanocrystal fluorescent microarray patterns based on photoinduced dehalogenation direct photolithography. Under the action of the mask, 254 nm ultraviolet light induces the dehalogenation of halogenated hydrocarbons to produce halogen ions and drive the generation of perovskite nanocrystals. By adjusting the pattern of the mask, different patterned perovskite nanocrystal fluorescent microarrays can be obtained without other operations such as development and etching. The method is very simple, efficient and low-cost. In addition, the display resolution DPI of the developed CsPbBr3 perovskite nanocrystal array can reach up to 1268, and the theoretical information storage capacity can reach 10 7502051 , and maintain good stability under polar solvent conditions, and based on the above strategy, a high-capacity macro-microstructure fluorescent anti-counterfeiting-encryption system is constructed. By switching between 365nm and 254nm excitation light sources, effective reading and dynamic erasure of information can be achieved, greatly improving information storage capacity and anti-cracking and attack capabilities. In addition, this strategy can be further extended to non-lead perovskite systems, such as copper-based, antimony-based, etc., and can also further expand its application areas, such as Micro-LED, sensor arrays, etc., with good scalability and application potential.

Claims

1. A fluorescent anti-counterfeiting and encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography, characterized in that: The following steps are involved: 1) dissolving cesium perfluoroglutarate, lead oleate and hexabromocyclododecane in N, N-dimethylformamide to obtain a perovskite precursor solution; 2) adding polymethyl methacrylate to the perovskite precursor solution, heating and stirring until completely dissolved to obtain a mixed precursor solution, coating the mixed precursor solution on a glass substrate to obtain a perovskite polymer precursor film, and then transferring it to a vacuum oven to dry and remove N, N-dimethylformamide; 3) A patterned chromium mask was covered on the perovskite polymer precursor film and irradiated under 254 nm ultraviolet light to obtain a CsPbBr3 fluorescent anti-counterfeiting array.

2. The fluorescent anti-counterfeiting and encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography according to claim 1, characterized in that: The usage ratio of cesium perfluoroglutarate, lead oleate, hexabromocyclododecane, N, N-dimethylformamide and polymethyl methacrylate is 0.06 mmol:0.06 mmol:0.1 mmol:2 mL:0.5 g.

3. The fluorescent anti-counterfeiting-encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography according to claim 1, characterized in that: Step 2) The heating temperature is 55-65°C.

4. The fluorescent anti-counterfeiting and encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography according to claim 1, characterized in that: Step 2) The coating method is spin coating with a rotation speed of 1000-1200 r / min.

5. The fluorescent anti-counterfeiting and encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography according to claim 1, characterized in that: Step 2) The temperature of the oven is 60-65°C, the pressure is 0.1 Mpa, and the drying time is 55-65 min.

6. The fluorescent anti-counterfeiting and encryption method based on in-situ synthesis of perovskite quantum dot arrays by solid phase photolithography according to claim 1, characterized in that: Step 3) The irradiation time under the ultraviolet lamp is 30 to 35 minutes.

Citation Information

Cited By

  • Photo-induced quantum dot in-situ growth method for coupling filling element defects and application

    CN121049225A